Heating of infusion fluids through heated breathing circuits - Kim, Myoung-hun; Kim, Ji-hoon; Hur, Dong-ki; Kim, Su-bin; Cho, Yong-hyun; Lim, Se Hun; Lee, Jeong-Han; Lee, Wonjin; Cho, Kwangrae (Anesthesia and pain medicine (Korean society of anesthesiologists), 2017)
Background: Hypothermia is a common physiological condition that occurs during surgical operations. The goal of this experiment is to measure the temperature of the fluids flowing through heated breathing circuits with respect to changes in infusion speed. Methods: The infusion pump was connected to the intravenous inlet of a heated breathing circuit with two 50 cm extension lines connected to the outlet. Fluids were injected through the heated breathing circuit at 100, 200, 300, 400, 500, 600, and 700 ml/h, with measurement of the fluid temperature immediately after transit (OP 20), 70 cm after transit (OP 70), and 120 cm after transit (OP 120). Results: The mean fluid temperatures at OP 20, OP 70, and OP 120 were 40.7 ± 4.8oC, 35.1 ± 3.22oC, and 31.7 ± 2.5oC, respectively. Conclusions: The heated breathing circuit was effective to heat the fluid. After passing out the heated breathing circuit, the temperature of the fluid continuously reduced. A length of 70 cm can be used to efficiently supply heated fluid to the patient. From this experiment, it is expected that supplying heated fluid to a patient using the heated breathing circuit will help maintain the patient's body temperature. KCI Citation Count: 0